Meeting Report: Fungal ITS Workshop (October 2012). Issue 1 (January 2013) - Bates, Scott; Ahrendt, Steven; Bik, Holly; Bruns, Thomas; Caporaso, J.; Cole, James; Dwan, Michael; Fierer, Noah; Gu, Dai; Houston, Shawn; Knight, Rob; Leff, Jon; et al.
Abstract This report summarizes a meeting held in Boulder, CO USA (19–20 October 2012) on fungal community analyses using ultra-high-throughput sequencing of the internal transcribed spacer (ITS) region of the nuclear ribosomal RNA (rRNA) genes. The meeting was organized as a two-day workshop, with the primary goal of supporting collaboration among researchers for improving fungal ITS sequence resources and developing recommendations for standard ITS primers for the research community.